(3GdTbGFb GdfYeGfjI aj YdeGA GdOhdI GdYKeGfjIs - (3WGTcHQj RGOI , YUGe GdOjf CHh GdNjQ CMeO Hf eUWaj Hf Ndjd, WGTcHQj RGOg,J (B968 (3g` s ((3eOjfI GdbSWfWjfjI s)
(3ChdgG (B:s
(3GdMeO ddg GdPi QaY HaVdg WHbGJ GdYdeGA , hLYd CUhd KGHJg haQhYge ai GdSeGA hdgPG CSeJ GdQSGdI HGdTbGFb GdfYeGfjI ai YdeGA GdOhdI GdYKeGfjI s
(3BNQgG (B:s
(3hdjS gPG hGdYjGP HGdgd EOYGA GddYe hGdaVjdI , adjcf gPG BNQ GdcJGH hbO aQZJ ef EedGFg HJGQN SfI NeS hSJjf , HeOjfI GdbSWfWjfjI s
(3cJHJ GdYfGhjjf HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B257s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs